Corporate Diversification and Corporate Social Performance in Indonesia - Dina Patrisia; Shabbir Dastgir; A. Abror (ETIKONOMI, 2019)
The relationship between corporate diversification and corporate social performance (CSP) is under-investigated, especially in emerging countries. This study examines the relationship between corporate diversification and CSP in Indonesia setting. Occurrence disclosure analysis has been applied to measure CSP based on 80 indicators of the Global Report Initiative (GRI). This study used multiple regressions with one-year lag dependent variables as the data analysis. The results show that the related diversification is negatively and significantly related to CSP, while, the unrelated diversification reveals a positive relationship with CSP. Besides that, unrelated diversification more correlated to CSP rather than related diversification. Furthermore, international diversification has a positive and significant relationship with CSP. Therefore, this study found that corporate diversification is a significant antecedent of CSP.JEL Classification: L25, M14